2003
DOI: 10.4269/ajtmh.2003.69.420
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Schistosoma Haematobium and Human Immunodeficiency Virus Type 1: The Effects of Coinfection on Treatment Outcomes in Rural Zambia

Abstract: A prospective cohort study was conducted in two villages in Zambia to compare the efficacy of praziquantel in the treatment of schistosomiasis haematobium in people with and without concomitant infection with human immunodeficiency virus (HIV). Five hundred seven individuals with infected with Schistosoma haematobium were enrolled and followed-up for as long as 12 months after treatment with a single dose of praziquantel. Seventy-three were coinfected with HIV. The study demonstrated that praziquantel is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 25 publications
6
57
2
Order By: Relevance
“…Other studies using a variety of diagnostic methods in various at-risk populations have shown a wide variance in schistosomiasis prevalence in endemic countries. Twenty per cent of adults in rural Nigeria [16], 40% of adults in rural Zambia [17], and 68% of children in rural South Africa [18] were infected with schistosomiasis. Among African migrants to Australia, 12% of those attending general practice in Melbourne [19] and 7% of those attending the Migrant Health Unit in Perth [20] were found to be infected with schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using a variety of diagnostic methods in various at-risk populations have shown a wide variance in schistosomiasis prevalence in endemic countries. Twenty per cent of adults in rural Nigeria [16], 40% of adults in rural Zambia [17], and 68% of children in rural South Africa [18] were infected with schistosomiasis. Among African migrants to Australia, 12% of those attending general practice in Melbourne [19] and 7% of those attending the Migrant Health Unit in Perth [20] were found to be infected with schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…One study along these lines showed that cure rates in HIV-positive subjects were as high as in HIV-negatives (Karanja et al 1998 ;Mwanakasale et al 2003), but the reason for this ' negative ' result may be that despite the viral infection the former already had the synergistically-active immune effector mechanisms in place.…”
Section: Mechanisms Of Action Of Pzq and Markers Of Resistancementioning
confidence: 99%
“…Schistosomiasis, in addition to its direct morbidity, may affect HIV-1 infection by causing general immune activation and by changing the pattern of cytokine secretion. Despite the large potential for dual occurrence of HIV-1 infection and schistosomiasis, only a few studies have described how these may interact [9][10][11][12][13]. These studies have suggested that an impaired schistosome egg excretion [9,10], a dysregulated immune response against schistosome infection [11], and even an increase in HIV-1 RNA load after praziquantel treatment [12,13] occur in individuals coinfected with HIV-1 and schistosomes.…”
Section: B R I E F R E P O R Tmentioning
confidence: 99%